AUGMENTED REALITY PENGENALAN MENU “POINT COFFEE” - Hardita, Veny Cahya; Elmayantie, Catharina; Kaharuddin, Kaharuddin (Jurnal Sains Komputer dan Teknologi Informasi, 2024)
Point Coffee Indomaret Fresh G. Obos has a hot/iced coffee menu provided. Many people do not know about composition of some coffee menus available. Sometimes it takes an explanation from the barista to find out the composition content of the Point Coffee menu. Another problem is that when there is a discount promotion, it does not exclude the possibility of a long enough queue so that it takes a lot of time for the barista to make a transaction while explaining the menu. In this study, the authors develop an application using Augmented Reality to introduce Point Coffee's existing coffee menu. The type of research used is Research and Development (R&D). Data collection techniques use interviews, documentation and library research. While Augmented Reality Application is based on marker. The development of this application uses Unity Engine and AR Core. An Augmented Reality application that features 6 (six) best seller main menus can be implemented in Point Coffee as an application which helps barista in explaining the main ingredients in the existing menu, as well as making it easier for customers to know the main ingredients of the drinks they are going to order. Keywords: Point Coffee, Indomaret, Augmented Reality, Unity, AR Core